Changes in Retinal Nonperfusion Associated with Suppression of Vascular Endothelial Growth Factor in Retinal Vein Occlusion - Mir, Tahreem A. (Ophthalmology, 2015)
PURPOSE: To assess changes in retinal nonperfusion (RNP) in patients with retinal vein occlusion (RVO) treated with ranibizumab (RBZ) DESIGN: Secondary outcome measure in randomized double-masked controlled clinical trial SUBJECTS: Thirty-nine patients with central RVO (CRVO) and 42 with branch RVO (BRVO) METHODS: Subjects were randomized to 0.5mg or 2.0mg RBZ every month for 6 months and then re-randomized to pro re nata (prn) groups RBZ+scatter photocoagulation (laser) or RBZ alone for an additional 30 months. MAIN OUTCOME MEASURES: Comparison of percentage of patients with increased or decreased area of RNP in patients with RVO treated with 0.5mg versus 2.0mg RBZ, during monthly injections versus prn RBZ, and in patients treated with prn RBZ versus prn RBZ+laser. RESULTS: In RVO patients given monthly injections of 0.5mg or 2.0mg RBZ for 6 months there was no significant difference in the percentage who showed reduction or increase in area of RNP. However, regardless of dose, during the 6 month period of monthly injections, a higher percentage of patients showed a reduction in area of RNP and a lower percentage showed an increase in area of RNP compared to subsequent time periods of prn RBZ treatment. After the 6 month period of monthly injections, BRVO, but not CRVO patients randomized to prn RBZ+laser showed significantly less progression of RNP compared to patients treated with prn RBZ. CONCLUSIONS: Regardless of dose of ranibizumab (0.5mg or 2.0mg), monthly injections promote improvement and reduce progression of RNP compared to prn injections. Addition of scatter photocoagulation to prn RBZ may reduce progression of RNP in patients with BRVO, but a statistically significant reduction was not seen in patients with CRVO.